Pulmonary metastases from low grade sarcoma in a patient with pulmonary sarcoidosis. Sarcoidosis or sarcoid-like reaction? - Majori, Maria; Anghinolfi, Miriam; Gnetti, Letizia; Casalini, Angelo Gianni (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
An asymptomatic man with previous histopatological diagnosis of pulmonary sarcoidosis in radiological follow-up (stable for about 4 years) presented massive right pleural effusion. After drainage, CT of the chest showed an increase in number and size of pulmonary nodules compared to the last check (8 months before). Surgical pulmonary biopsies were performed with the diagnosis of metastases from low grade sarcoma. The primary tumor was localized to the right buttock. Given the absence of symptoms, the extent of disease and many comorbidities the patient underwent only treatment with gemcitabine that was not tolerated and discontinued after the first few cycles 1 year ago. At the present the patientis still asymptomatic even if the CT of the chest shows a slow but continuous progression of the disease. The question is: is this an association between sarcoidosis and malignancy? or was this a sarcoid-like reaction during malignancy?